The Mediating Role of Self-Efficacy in Factors Influencing MSME Performance Improvement - Nugroho, Mahfud; Cahyo, Septian Dwi; Saraya, Sitta; Astuti, Fitria Yuni (International Journal of Economics Development Research (IJEDR), 2025)
After the Covid-19 pandemic ended, MSMEs selling online increased. However, price competition in the digital market is very tight, so MSMEs with small capital cannot compete with large companies that have entered the digital market first. The aim of this research is to analyze the impact of using digital marketing, financial inclusion and financial literacy on business performance which is mediated through self-efficacy. This research tests causality through a quantitative approach. The population in this study was 100 MSMEs in Kendal, Indonesia. The sample in this study was selected based on purposive sampling with certain criteria. The data analysis method uses linear regression analysis which is tested statistically via SmartPLS. The results of this research found that the use of digital marketing can influence or improve business performance. The use of digital marketing can also increase the self-confidence of MSMEs in managing their business (self efficacy). Ease of access to use financial products and services (Financial inclusion) can improve business performance. Then the ease of accessing financial products and services can also increase self-confidence to be successful (self-efficacy) in managing a business. Self-efficacy cannot mediate the influence of digital marketing, financial literacy and financial inclusion on business performance